2020
DOI: 10.1002/smll.202002201
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High‐Performance Perovskite Photovoltaic by Morphology Engineering of Low‐Temperature Processed Zn‐Doped TiO2 Electron Transport Layer

Abstract: Perovskite solar cells (PSCs) have become one of the most promising renewable energy converting devices. However, in order to reach a sufficiently high power conversion efficiency (PCE), the PSCs typically require a high‐temperature sintering process to prepare mesostructured TiO2 as an efficient electron transport layer (ETL), which prohibits the PSCs from commercialization in the future. This work investigates a low‐temperature synthesis of TiO2 nanocrystals and introduces a two‐fluid spray coating process t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The E fb of CuO was very close to its E VB , also indicating its p-type conductivity, while the E fb of CuHCF was very close to its E CB , also denoting that it was an n-type semiconductor. 32 n-Type materials were often adopted as electron transporters in solar cells, 9 and we speculated that the spontaneously formed CuHCF also acted as an electron transporting material for CuO to induce the improved charge separation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E fb of CuO was very close to its E VB , also indicating its p-type conductivity, while the E fb of CuHCF was very close to its E CB , also denoting that it was an n-type semiconductor. 32 n-Type materials were often adopted as electron transporters in solar cells, 9 and we speculated that the spontaneously formed CuHCF also acted as an electron transporting material for CuO to induce the improved charge separation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast to the state-of-the-art cathodic photoelectrochemistry that relies on diffusive electron accepting molecules in solution for signal stimuli, research in solar cells have demonstrated that some solid materials can extract and transport photogenerated electrons of semiconductors, which significantly dictate the overall photovoltaic performances (such as the photo-to-current conversion efficiency) . The recently booming investigations using organic (such as naphthalene diimides (NDIs) and perylene diimides (PDIs)) and inorganic (such as TiO 2 , ZnO, and SnO 2 ) solid materials as electron transporting scaffolds have shown encouraging performances in promoting anodic photocurrent generation of perovskites. Search on electron transporters applicable to p-type semiconductors is rarely reported because the solar cell research focuses on n-type semiconductors as the photoactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…This nanostructure would make the perovskite layer thicker than other planar structures in previous reports. [26] Unfortunately, the bare ZnO NRs may have some defects, making the perovskite film exist some pinholes or other questions. From the Figure 2a, it is obvious that a few pinholes are scattered on perovskite film deposited on bare ZnO NRs, which can attribute to the presence of hydroxyl groups or acetate ligands on the surfaces of ZnO NRs.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The parameters that significantly influence the formation of anatase include procedural reaction time, pressure and temperature. Besides these, secondary operation during synthesis also play crucial part in the formation of anatase [31][32]. Whereas chemical composition, morphology and composition of phase can be optimized by pH, and temperature by employing hydrothermal and sol-gel techniques [33].…”
Section: Introductionmentioning
confidence: 99%